Government of Canada fixed-income market ecology - Léanne Berger-Soucy; Corey Garriott; André Usche (Bank of Canada, 2018)
This discussion paper is the third in the Financial Markets Department's series on the structure of Canadian financial markets. These papers are called "ecologies" because they study the interactions among market participants, infrastructures, regulations and the terms of the traded contract itself. In this ecology, we discuss the Government of Canada's domestic fixed-income market. We begin with an overview of Government of Canada securities and their characteristics. We then outline common market practices and the typical participants in the market. We provide high-level statistics on activity in the market and describe the market infrastructures that support trading. Finally, we discuss risks in these securities markets.
Keywords: G10; G20; H63; 330; Financial markets; Debt management; Financial institutions; Financial services